PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PADA PEMBELIAN PT. SHOPEE INTERNATIONAL INDONESIA DI KOTA SUKABUMI - Umban Adi Jaya; Ananda Mutiara (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study aims to determine the effect of promotion and price on purchasing decisions at PT. Shopee International Indonesia in the city of Sukabumi, where Shopee consumers in the city of Sukabumi also often shop through this application by looking at the promotions that PT. Shopee International Indonesia often holds and the prices offered so that in purchasing decisions there are several factors that influence in it, and this research the writer takes the promotion and price factors. In this research quantitative associative research is used with data collection techniques by observation and questionnaire. The analysis technique used is the validity test, reliability test, normality test, multiple linear regression analysis, coefficient of determination analysis. In testing the hypothesis using partial test and simultaneous test. Based on the results obtained from this study, it shows that the influence of promotion is 52.9% and the influence of price is 40.3%. and the effect of promotion and price simultaneously that is equal to 56.6% while the remaining 43.4% is explained by other variables not included in this study that include products, places, people, processes, advertising, physical evidence.